Increased immediate postoperative hemorrhage in older and obese children after outpatient tonsillectomy. (May 2016) - Kshirsagar, Rijul; Mahboubi, Hossein; Moriyama, Derek; Ajose-Popoola, Olubunmi; Pham, Nguyen S.; Ahuja, Gurpreet S.
Abstract: Introduction: Postoperative hemorrhage is one of the serious complications of adenotonsillar surgery. This study seeks to investigate the relationship between post-tonsillectomy/adenotonsillectomy hemorrhage in the pediatric population and obesity, obstructive sleep apnea (OSA), adenotonsillar hypertrophy (ATH), chronic tonsillitis (CT), and peritonsillar abscess (PTA) in the immediate post-operative setting. Methods: The California Ambulatory Surgery Data for the years 2005–2011 were reviewed. The records of patients aged less than 18 years undergoing tonsillectomy (T) or adenotonsillectomy (AT) were extracted using relevant ICD-9 diagnosis codes. The association between hemorrhage and obesity, OSA, AH, CT, PTA, and patients' demographics among surgeries performed in the outpatient setting was evaluated. Results: A total of 138, 998 procedures, 22, 478 Ts and 116, 520 ATs, were performed during 2005–2011, of which 3.0% were performed on obese children. Hemorrhage occurred in 156 cases (0.1%), and was associated with an age from 9 to 18 years ( p  = 0.01), and obesity ( p  = 0.02). There was no association between hemorrhage and gender ( p  = 0.8), OSA ( p  = 0.6), ATH ( p  = 0.5), CT ( p  = 0.35), PTA ( p  = 0.47), or T versus AT ( p  = 0.3). Multivariate analysis revealed that hemorrhage was about 2.3 times more likely to occur in obese children (odds ratio [OR] = 2.3; 95% Confidence Interval: 1.1–5.1; p  = 0.03). Conclusions: Obesity and older age are associated with an increased risk of immediate post-operative hemorrhage following tonsillectomy with or without adenoidectomy in the outpatient setting. Gender, OSA, ATH, CT, PTA, and T versus AT did not alter the risk of post-operative hemorrhage.